Solution techniques for multi-physics problems with application to computational nonlinear aeroelasticity - Soulaı¨mani, Azzeddine; Feng, Zhengkun; Ben Haj Ali, Amin (Nonlinear analysis, 2005)
This paper presents an efficient parallel-distributed methodology for solving multi-physic problems. This methodology is based on functional and geometric decompositions. Solution algorithms for coupled problems are discussed. All these techniques are illustrated for the case of CFD-based aeroelasticity. A numerical study is performed for the Agrad 445.6 aeroelastic test case.